An Interstitial Deletion at 7q33-36.1 in a Patient with Intellectual Disability, Significant Language Delay, and Severe Microcephaly. (8th December 2016) - Kale, Trupti; Philip, Melissa
Abstract : Interstitial deletions of the distal 7q region are considered a rare entity. In this report, we describe a seven-year-old male with a heterozygous interstitial deletion at 7q33-36.1 with characteristic dysmorphic facial features, intellectual disability, severe microcephaly, and significant language delay. The primary focus of our report is to compare our case with the few others in the literature describing interstitial deletions at the long arm of chromosome 7. Based on the various breakpoints in prior studies, a number of phenotypic variations have been identified that are unique to each of the reports. However, there are also a number of similarities among these cases as well. We hope to provide a concise review of the literature and genes involved within our deletion sequence in the hope that it will contribute to creating a phenotypic profile for this patient population.